Terrier - Pierce, Tamora (New York : Random House Children's Books, 2006)
When sixteen-year-old Beka becomes "Puppy" to a pair of "Dogs," as the Provost's Guards are called, she uses her police training, natural abilities, and a touch of magic to help them solve the case of a murdered baby in Tortall's Lower City.
"A Tortall legend"--Jacket.
Maps on endpapers.
Keywords: Police -- Juvenile fiction; Magic -- Juvenile fiction; Police -- Fiction; Magic -- Fiction; Fantasy